Distinctive circulating microbial metagenomic signatures in the plasma of patients with lung cancer and their potential value as molecular biomarkers - Huijuan Chen; XueNa Yao; Chunyan Yang; Yiran Zhang; Henan Dong; Jincheng Zhai; Dongjie Fan; Qiming Zhou (Journal of Translational Medicine)
Abstract Lung cancer (LC) remains the leading cause of cancer death globally. Recent reports have suggested that circulating microbial nucleic acids have potential as promising biomarkers for cancer liquid biopsies. However, circulating microbial profiles and their potential clinical value in LC patients remained unexplored. In this study, plasma samples from 76 LC patients, 9 liver cancer patients, 11 pancreatic cancer patients, and 53 healthy controls (HCs) were collected and underwent metagenomic analyses by whole genome sequencing. The composition and relative abundance of the microbial profiles were significantly different between the LC patients and HCs. A distinct plasma-based microbial profile was observed in LC patients. By differential analysis using MaAslin, 40 significant species between LC patients and HCs were identified. Five species were selected as optimal circulating microbial biomarkers for LC. The constructed classifier based on these five species showed an AUC of 0.9592, 0.9131, and 0.8077 in the discovery, validation, and additional validation cohorts, respectively. Furthermore, metagenomic profiles of 25 lung tumor tissue and plasma paired samples were analyzed and compared. The microbial diversity was significantly increased in plasma compared with the tumor tissue. Among the 13 shared core microbial species, 10 had no difference between the tumor tissue and paired plasma. In conclusion, circulating microbial nucleic acids in the plasma have potential as biomarkers for LC liquid biopsies. The microbiome in the tumor tissue was one of the possible sources of circulating microbial nucleic acids.